2012
DOI: 10.1103/physrevb.85.184434
|View full text |Cite
|
Sign up to set email alerts
|

Realization of the one-dimensional anisotropicXYmodel in a Tb(III)-W(V) chain compound

Abstract: We report the magnetic behavior of the one-dimensional (1D) cyanido-bridged chain complex [Tb(pzam) The system shows qualitatively similar magnetic behavior with its already reported M = Mo(V): a broad anomaly in the specific heat ascribed to the magnetic interactions, a transition to three-dimensional magnetic order at T C = 1.15 K, and comparable magnetization and susceptibility. However, substituting the Mo(V) ion by the larger W(V) causes a drastic change in the symmetry of the Tb(III) g tensor, whereby t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this respect, it deserves to be noted that weak ferro- or antiferromagnetic interactions were reported in previous magneto-structural studies concerning cyanido–bridged compounds with these metal ions. So, for previously reported examples of chains, layers, ,, and 3D networks enclosing cyanido-bridged {Tb III W V } pairs, the magnetic coupling is found weakly ferromagnetic. Also, very weak ferromagnetic interactions between Dy III and W V through a single-cyanide bridge were observed in the hetero-dinuclear complex [Dy III (terpy)­(DMF) 4 ]­[W V (CN) 8 ]·6H 2 O·8EtOH (terpy = 2,2′:6′,2″-terpyridine; DMF = dimethylformamide; J DyW = +0.23 cm –1 ) and in the chain compound [Dy III (pzam) 3 (H 2 O)­W V (CN) 8 ]·H 2 O (pzam = pyrazine-2-carboxamide), which account for the increase of χ M T at very low temperatures in their respective χ M T against T plots.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In this respect, it deserves to be noted that weak ferro- or antiferromagnetic interactions were reported in previous magneto-structural studies concerning cyanido–bridged compounds with these metal ions. So, for previously reported examples of chains, layers, ,, and 3D networks enclosing cyanido-bridged {Tb III W V } pairs, the magnetic coupling is found weakly ferromagnetic. Also, very weak ferromagnetic interactions between Dy III and W V through a single-cyanide bridge were observed in the hetero-dinuclear complex [Dy III (terpy)­(DMF) 4 ]­[W V (CN) 8 ]·6H 2 O·8EtOH (terpy = 2,2′:6′,2″-terpyridine; DMF = dimethylformamide; J DyW = +0.23 cm –1 ) and in the chain compound [Dy III (pzam) 3 (H 2 O)­W V (CN) 8 ]·H 2 O (pzam = pyrazine-2-carboxamide), which account for the increase of χ M T at very low temperatures in their respective χ M T against T plots.…”
Section: Resultsmentioning
confidence: 64%
“…Eight-coordinate [M m (CN) 8 ] (8– m )– complexes represent a versatile class of cyanide-based metalloligands that proved to be a suitable platform to assemble functional molecular materials (M = Mo and W and m = 4 or 5). In past decade, the complexes including cyanido-bridged {Ln III M IV/V } pairs of ions have received an increasing attention, the large coordination number of the trivalent rare-earth cations, the high denticity of the M IV/V from the cyanide-bearing metalloligand, and the flexible molecular geometry of the octacyanometallate units affording a variety of extended structures with different topologies (M = Mo and W). The systems comprising rare-earth ions and paramagnetic [M V (CN) 8 ] 3– moieties are particularly interesting. The overlap between the diffuse magnetic 4(5)­d orbitals of M V cations and the inner 4f orbitals of the lanthanide­(III) ions leads to ferromagnets, , short- to long-range ferromagnetic transitions, and coexistent magneto-optical properties. The single-ion anisotropy and large spin value of the ground state of the Ln III ions is very appealing for the design of d–f nanomagnets .…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Bernot et al reported a series of rare earth element based single chain magnet using radical as a bridging ligand, where Tb(III) based SCM has also been reported [18]. In 2012, Pasca et al reported a cyanido bridged one dimensional chain of tungsten and terbium [42]. In 2012, Liu et al and in 2014, Hu et al reported Tb(III) based 1D chain where the bridging ligand was the basic unit of nitronyl nitroxide based radical [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, quantum spin chains in many cases are amenable to rigorous analysis that permits to obtain results free of using any uncontrolled approximations [4][5][6][7][8] . At the same time, real solid-state representatives of exactly solved quantum spin-chain models have become available due to a recent progress in material sciences and comparison of theoretical predictions with experimental observations has thus become possible 3,9 .…”
Section: Introductory Remarksmentioning
confidence: 99%